Political Economy of State Intervention in the “Regional Problem”: Insights from the Savannah Accelerated Development Programme (SADEP) – Ghana - Adam Mohammed, Abdul-Wadudu (Advances in Social Sciences Research Journal, 2019)
This paper examines state intervention in the regional problem in Ghana using documentary case study of the Savannah Accelerated Development Programme (SADEP). The findings suggest that SADEP has been ineffective (less successful) in transforming the economy of the Northern Savannah Ecological Zone (NSEZ). This is because, first, of improper/ineffective dispensation of authority though this is not political settlement issue. Second, because of corruption and financial mismanagement and misappropriation. Lastly, because of inadequate attention to implicit polarisation policies. These imply the need for effective accountability mechanisms including active civil society and media; incentives structure that is divorced from partisan politics and integration of implicit polarisation reduction strategies into regional development programmes for distressed regions in Ghana.